Pre-Export Planning and Start-up Export Performance for Small Electronics Manufacturers (Journal of Small Business Strategy (archive only), 1996)
An increasing number of small businesses are seeking customers in foreign countries. At this time, however, our knowledge of small business successful export practices is limited. To increase our export understanding, it has been suggested that research should examine in more depth the relationship between export planning and performance.   Based on a sample of eighteen small firms in the electronics industry, weak support was found for the hypothesis that the level of formal export planning is positively related to export performance. Areas for future research and limitations of the study are also discussed.